Pengaruh Model Pembelajaran SAVI (Somatis, Auditori, Visual, Intelektual) terhadap Keterampilan Menulis Teks Eksposisi Siswa Kelas X SMA N 14 Medan - Ayu Permatasari Sihotang; M. Joharis Lubis (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
One of the aims of this research is to identify students' writing skills taught by the Somatic, Auditory, Visual and Intellectual (SAVI) learning model in expository texts written by students in class X SMA N 14 Medan. Another aim is to find out how the problem-based learning model (PBL) and the SAVI (Somatic, Auditory, Visual and Intellectual) learning model have an impact on the exposition text. This research involved all students in class X SMA N 14 Medan, with a simple random sample, consisting of 36 students in class X-1 and 36 students in class X-2. A two-group post-test experimental method was used and the research instrument was an expository text writing test. The "t" test data is used to test the hypothesis. The results show that students' ability to write expository texts using the PBL learning model is in the fair category with an average score of 70.36, while their ability with the SAVI learning model is in the very good category with an average score of 89.36. Furthermore, the results of the hypothesis test show that the null hypothesis (H0) is rejected, and the alternative hypothesis (Ha) is accepted, because tcount is greater than ttable, namely 9.82 is greater than 1.934. Thus, it can be concluded that the expository text writing skills of class X SMA N 14 Medan students are greatly influenced by the use of the SAVI learning model.